The impact of managing employees’ performance in building intellectual capital Analytical study of the views of a sample of heads of scientific departments At the University of Kirkuk - عوض عبد الستار سالم; سلمان منصور; صالح ثابت علي (Journal of Economics and Administrative Sciences, 2018)
The research aims to identify the impact of managing performance’s employees in building intellectual capital, Because employing the practice of managing the performance of employees may acquire familiar skills to improve their performance and reflect on the construction of intellectual capital in the surveyed area, Especially that the independent dimension represented by the management of the performance of employees is one of the important topics that has received attention in the world of management in general and human resource management in particular. While the adopted dimension was represented by Intellectual capital in the important practice of human resource management in the increasing of their knowledge, to achieve the goal of the research, the researchers relied on the questionnaire as a data collection tool which distributed to a sample its size (46) from head of department at the University of Kirkuk. And through statistical analysis of data using the program (SPSS.24) It was found that there is a correlation relationship and a significant effect on the managing performance’s employees in the building intellectual capital in the organization which is surveyed, the organization mast improve the management by encourage performance of its employees and by supporting their needs, As well as improving the expertise and competencies which is necessary for sustainability and investment, and saving human resources and raise the level of performance in the organization that is surveyed